Logam Berat Pb, Cu, Zn Dan Ni Dalam Air Di Ekosistem Lamun Pulau Pahawang - Ariqoh Athallah Gusri; Rozirwan Rozirwan; Wike Ayu Eka Putri (Universitas Bangka Belitung, 2025)
In coastal environments and the ecosystems, including seagrass ecosystems, heavy metals can lead to pollution. This study goal is to analyze the concentration of heavy metals in water based on safety standards for marine organisms. Water samples were collected from two locations: Jeralangan HamLet and Cukuh Nyai HamLet in Pahawang Island, Lampung, Indonesia. Water quality parameters were measured in situ. Heavy metals such Pb, Cu, Ni, and Zn were prepared using Wet digestion method and the concentrations were measured using Atomic Absorption Spectrophotometer (AAS) SHIMADZU AA-7000. At the same location, the highest concentration of was observed for Zn 0.406 mg/L at station 2, while the lowest concentration was recorded for Cu 0.019 mg/L. The concentration of heavy metals Pb, Cu, Ni and Zn in water has exceeded the quality standards for marine biota and marine tourism.These research can be used as a basis for future planning in the management of Pahawang Island’s coastal environment.